Perspectivas ambientais no setor supermercadista e suas ações de compras sustentáveis aplicadas em redes de varejo de Mossoró (RN) - Silva, Tâmara Claude de Oliveira (Universidade Federal Rural do Semi-Árido, 2017)
The organizations today understand that in addition to giving people a better quality of life through the products they offer in their business, they still need to present to them the way they are thinking about the environment. Companies in the supermarket sector, for example, became aware of the fact that their customers adhere to returnable bags, eliminating the plastic bags that caused so much disruption to nature as expenses for the company itself and customers. Therefore, the rationale of this paper is: To identify the socio-environmental actions developed by the supermarket in the city of Mossoró / RN; Relate actions to sustainable purchasing practices; Identify the motivations for implementing sustainable practices in retail. In order to answer the research questions, a survey of data was carried out through the study of a case, where the collection occurred before a semi-structured interview that contains 21 questions, in order to better understand how the company behaves in the market monitoring as specifications for the welfare of the client and society as a whole in terms of sustainability. It should be noted that the objectives of the work were fulfilled when it is possible to better understand the sustainable purchasing dynamics of the researched company, together with buyers specialized in diversified branches, who can discuss how external negotiations work in defense of purchases of products that do not interfere with the quality of life of human beings or cause shortages in natural resources.
Monografia
Keywords: Compras; Varejo; Processos; Supermercados; Sustentabilidade; Shopping; Retail.; Processes; Supermarket; Sustainability; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO